Tongiaki to Kalia: The Micronesian-rigged Voyaging-canoes of Fiji and Western Polynesia and their Tangaloan-rigged Forebears - Clunie, Fergus (Waka Kuaka, 2016)
This article draws upon a wide ranging combination of historical traditions, documentary history and archaeology to demonstrate that Tangaloan-rigged Tongan tongiaki and hamatefua voyaging canoes were of mixed autochthonous Melanesian and intrusive Tangaloan descent, and that the Micronesian-rigged drua/kalia and camakau/hamatefua voyaging canoes which succeeded them in Fiji and Western Polynesia were developed from them as an outcome of Tongan adoption of the Micronesian rig in the 18th century, and the corresponding transfer of voyaging canoe construction from Samoa to Fiji.